Assessment of energy efficiency of high-voltage LUE modulators - Kosoy, O.I.; Matz, V.O.; Romasko, V.P.; Titarenko, Yu.A.; Tytov, V.Yu.; Titov, D.V.; Tur, Yu.D.; Chaika, I.O.; Chertishchev, I.A.; Yaroshenko, E.A. (Вопросы атомной науки и техники, 2020)
An assessment of the energy efficiency of pulse modulators of technological accelerators at the NSC KIPT. The influence of the parameters of a pulse transformer on a voltage pulse at a load is investigated. The possibilities of increasing the energy efficiency of plants are considered. Studies of losses in high-voltage pulse modulator systems were conducted and it was shown that the main elements that require replacement or improvement are forming lines and pulse transformers.